APLIKASI PENJUALAN BARANG SEMBAKO MENGGUNAKAN VISUAL STUDIO - Imanuel Tarigan (UPPM, 2019)
The development of technology has spread throughout the world and even across the boundaries of thelives of many people. The development of companies engaged in the business sector, for example,business entity institutions in the sale of goods. These goods sales activities often experience variousproblems that may arise in the activities of the report, so it takes a long time to make a report. Computersfor example, the existence of this object makes it possible no longer need to do the tedious tasks,especially in the activities of selling groceries manually but it requires a long time. For that reason, theauthor tries to design a computer-based application that is expected to be able to overcome the variousweaknesses of a manual work system that is currently running, especially information on selling groceriesin stores.